Allicin affects immunoreactivity of osteosarcoma cells through lncRNA CBR3-AS1 - Wenpeng Xie; Fengjun Ma; Luming Dou; Wenjie Chang; Daotong Yuan; Zhimeng Zhang; Yongkui Zhang (Heliyon, 2024)
Objective: To analyze the effect of allicin on the immunoreactivity of osteosarcoma (OS) cells and further explore whether its mechanism is related to the long non-coding Ribonucleic Acid (lncRNA) CBR3-AS1/miR-145-5p/GRP78 axis, so as to provide clinical evidence. Methods: The human OS cell line Saos-2 was treated with allicin at 25, 50, and 100 μmol/L, respectively, to observe changes in cell biological behaviors. Subsequently, CBR3-AS1 abnormal expression vectors were constructed and transfected into Saos-2 to discuss their influence on OS. Furthermore, the regulatory relationship between allicin and the CBR3-AS1/miR-145-5p/GRP78 axis was validated by rescue experiments. Finally, a nude mice tumorigenesis experiment was carried out to analyze the effects of allicin and CBR3-AS1/miR-145-5p/GRP78 axis on the growth of living tumors. Alterations in T-lymphocyte subsets were also detected to assess the effect of allicin on OS immunoreactivity. Results: With the increase of allicin concentration, Saos-2 activity decreased and apoptosis increased (P < 0.05). In addition, the expression of CBR3-AS1 and GRP78 decreased after allicin intervention, while miR-145-5p increased (P < 0.05). Silencing CBR3-AS1 led to reduced Saos-2 activity, enhanced apoptosis, and activated mitophagy and endoplasmic reticulum stress (P < 0.05). In the rescue experiment, the effect of CBR3-AS1 on OS cells was reversed by silencing miR-145-5p, while the impact of miR-145-5p was reversed by GRP78. Finally, the tumorigenesis experiment in nude mice confirmed the regulatory effects of allicin and CBR3-AS1/miR-145-5p/GRP78 on tumor growth in vivo. Meanwhile, it was seen that allicin activated CD4+CD8+ in OS mice, confirming that allicin has the effect of activating OS immunoreactivity. Conclusions: Allicin activates OS immunoreactivity and induces apoptosis through the CBR3-AS1/miR-145-5p/GRP78 molecular axis.